2009
DOI: 10.1007/s10457-009-9235-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and photosynthetic alterations in the Yellow-ipe, Tabebuia chrysotricha (Mart. Ex DC.) Standl., under nursery shading and gas exchange after being transferred to full sunlight

Abstract: The objective of this study was to evaluate the effect of nursery shading on the Yellow-ipe seedling (Tabebuia chrysotricha) growth, photosynthesis, and photosynthetic acclimation after being transferred into direct sunlight. The Yellow-ipe seedlings were grown under 0, 50, 70 and 95% shade. At the 134th day of sowing, leaf gas exchange and chlorophyll were measured under current growth shading, after exposure to 15 min and two day full sunlight. With the increase of shading, the Yellow-ipe seedlings allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Several studies emphasized the importance of environmental conditions for leaf gas exchange. Endres et al (2009) found that light environment influence the CO 2 fixation. The correlation between PAR (photosynthetic active radiation) and photosynthetic rate of Tabebuia chrysotricha differs depending on light environment: the correlation was stronger (R 2 =0.6699) at plants grown under shade and lower (R 2 =0.29) at plants grown in sunlight.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies emphasized the importance of environmental conditions for leaf gas exchange. Endres et al (2009) found that light environment influence the CO 2 fixation. The correlation between PAR (photosynthetic active radiation) and photosynthetic rate of Tabebuia chrysotricha differs depending on light environment: the correlation was stronger (R 2 =0.6699) at plants grown under shade and lower (R 2 =0.29) at plants grown in sunlight.…”
Section: Review Of Literaturementioning
confidence: 99%
“…1). The different PAR may greatly influence the photosynthetic activity of plants (Endres et al, 2009). These values were measured in a period from 12 am to 14 pm which means the highest radiation during the day.…”
Section: Photosynthetic Active Radiation (Par) Values Measured On Leafmentioning
confidence: 99%
“…Changes in the number of leaves were not observed in Hymenaea parvifolia (Silva et al, 2007) under up to 70% shade at 105 days after planting, Simarouba amara Aubl under up to 70% shade at 182 days after germination (Azevedo et al, 2010) or Caesalpinia echinata Lam under up to 80% shade analysed at 12, 18 and 24 months after germination (Aguiar et al, 2005). Moreover, Fonseca et al (2002) found reductions in the number of leaves in Trema micrantha (L.) Blume grown under 48% shade at 120 days after germination, while Endres et al (2010) reported a significant increase in the number of leaves in Tabebuia chrysotricha, especially those grown under 70% shade at 130 days after planting.…”
Section: Resultsmentioning
confidence: 99%
“…However, in plants subjected to environments with more light, the leaf area is decreased, which is beneficial to the plant given that less leaf material is exposed to potential damages The dry mass allocation to the root system of T. aurea ranged from 13% (under 95% shade) to 24% (under full sunlight, Figure 3B). Silva et al (2007) and Endres et al (2010) observed reductions in the dry mass of the root systems of Hymenaea parvifolia and Tabebuia chrysotricha plants, respectively, under 70% shade, while Dantas et al (2009) observed no significant differences in the dry masses of roots in seedlings of Caesalpinia pyramidalis Tul. grown under 75% shade at 100 days after sowing.…”
Section: In Caesalpinia Pyramidalismentioning
confidence: 97%
See 1 more Smart Citation